Enhancing 2-Ketogluconate Production of Pseudomonas plecoglossicida JUIM01 by Maintaining the Carbon Catabolite Repression of 2-Ketogluconate Metabolism - Wenjing Sun; Tjahjasari Alexander; Zaiwei Man; Fangfang Xiao; Fengjie Cui; Xianghui Qi (Molecules, 2018)
2-Ketogluconate (2KGA) is an organic acid that is important for pharmaceutical, cosmetic, and environmental applications. Pseudomonas plecoglossicida JUIM01 strain is an important industrial 2KGA producer in China. In this paper, we found that P. plecoglossicida JUIM01 could convert glucose to 2KGA extracellularly, and the formed 2KGA was subsequently consumed after glucose was exhausted during the fermentation process. Experiments of glucose and 2KGA supplementation during fermentation process revealed that, only when glucose was exhausted, the strain started to consume the product 2KGA. Then, the mechanism of this phenomenon was investigated at transcription and protein levels, and the results indicated that P. plecoglossicida JUIM01 possesses carbon catabolite repression of 2KGA metabolism by glucose. Next, increasing the supply of glucose could attenuate 2KGA consumption and enhance the 2KGA yield from glucose. Finally, fed-batch fermentation of P. plecoglossicida JUIM01 resulted in 205.67 g/L of 2KGA with a productivity of 6.86 g/L/h and yield of 0.953 g/g glucose. These results can provide references for the industrial fermentation production of 2KGA and other fermentation products.